2018
DOI: 10.6065/apem.2018.23.1.4
|View full text |Cite
|
Sign up to set email alerts
|

Small for gestational age and obesity related comorbidities

Abstract: Infant born small for gestational age (SGA) are at increased risk of perinatal morbidity, persistent short stature and metabolic alterations in later life. The result of SGA followed by rapid weight gain during early postnatal life has been associated with increased long-term risks for central obesity, insulin resistance, impaired glucose tolerance, type 2 diabetes, hypertension, increased fat mass, and cardiovascular disease. We should carefully monitor their weight during infancy and childhood to prevent exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
58
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(67 citation statements)
references
References 57 publications
0
58
0
5
Order By: Relevance
“…In addition, some authors demonstrated that asthma and its treatment with inhaled corticoids delayed the pubertal timing [32,33], although findings were controversial about this subject [34]. However, Childhood obesity accelerates the age of puberty and menarche [35,36], noting that premature and SGA infants are at a higher risk to develop obesity later on [37,38]. Psychosocial factors, such as family disruption, father's absence and continuous stress also seem to lead to a more precocious sexual maturation and menarcheal age [22], especially if these factors occur during early childhood (before the age of 5 years where girls seem to be the most sensitive to family composition).…”
mentioning
confidence: 99%
“…In addition, some authors demonstrated that asthma and its treatment with inhaled corticoids delayed the pubertal timing [32,33], although findings were controversial about this subject [34]. However, Childhood obesity accelerates the age of puberty and menarche [35,36], noting that premature and SGA infants are at a higher risk to develop obesity later on [37,38]. Psychosocial factors, such as family disruption, father's absence and continuous stress also seem to lead to a more precocious sexual maturation and menarcheal age [22], especially if these factors occur during early childhood (before the age of 5 years where girls seem to be the most sensitive to family composition).…”
mentioning
confidence: 99%
“…Globally, 16% of infants are small for gestational age (SGA, birth weight for gestation <10th percentile) at birth, with frequencies ranging from 7% in industrialized countries to 41.5% in South Asia (11). SGA infants are at increased risk for negative developmental and adult health outcomes, including lower psychological and intellectual performance and increased risk for precocious puberty, type 2 diabetes, metabolic syndrome, obesity, and CVD (12)(13)(14). Most SGA infants catch up with their appropriate-for-gestational-age (AGA, birth weight for gestation ≥10th to <90th percentiles) counterparts by exhibiting a faster rate of weight and length gain, with the percentiles on the growth charts crossing upward.…”
Section: Original Articlementioning
confidence: 99%
“…Childhood obesity can be associated with neonates born heavy for height as well as light for height with associated "catch-up" excessive weight gain [7][8][9]. Internal obesity in the first postnatal months increases the risk of the later development of type 2 diabetes, metabolic syndrome, and cardiovascular and nervous system pathologies [10][11][12]. Such data highlights the importance of the prenatal period in modulating obesity predisposition as well as in indicating the important role that pregnancy has as an "environmental sampling" period for adaptive development.…”
Section: Introductionmentioning
confidence: 99%